Modelling of hydrogen transport in silicon solar cell structures under equilibrium conditions - Hamer, P (University of Oxford, 2018)
The files consist of matlab scripts and matlab workspaces. The workspaces are the results of running the scripts (hydrogentransport.m) in Matlab R2016b over the last 3 months. Other information of importance is the values within the workspaces: